Transforming health markets in Asia and Africa : improving quality and access for the poor - Bloom, Gerald. (Pathways to sustainability series, 2013)
"Markets for health-related goods and services have spread rapidly in many low and middle-income countries. This has substantially increased the availability of health-related goods and services, but it has created problems with safety, efficacy and cost. Making Health Markets Work addresses the challenge of improving health markets so that they better meet the needs of the poor.This book gathers together for the first time information about these little understood yet pervasive systems and offers evidence-based recommendations for policy-makers and private and public sector health managers. It presents a new way of understanding highly marketized health systems, applies this understanding to an analysis of health markets in countries across Asia and Africa and identifies some of the major new developments for making these markets perform better in meeting the needs of the poor"--Provided by publisher.